Spatiotemporal modeling of fuelwood environmental impacts: Towards improved accounting for non-renewable biomass. (August 2016) - Ghilardi, Adrián; Bailis, Robert; Mas, Jean-François; Skutsch, Margaret; Elvir, José Alexander; Quevedo, Alexander; Masera, Omar; Dwivedi, Puneet; Drigo, Rudi; Vega, Ernesto
Abstract: The extraction and burning of woody biomass at rates exceeding re-growth (i.e. non-renewable extraction) results in net emissions of CO2 . Quantification of the amount of non-renewable woody biomass through a robust and widely applicable method is urgently needed for a wide variety of applications including cookstove carbon-offset projects, national GHG inventories, and sustainable forest management strategies under REDD+. Within this context, we developed "Mofuss" (Modeling fuelwood savings scenarios), a dynamic model that simulates the spatiotemporal effect of fuelwood harvesting on the landscape vegetation and that accounts for savings in non-renewable woody biomass from reduced consumption. The model was tested in western Honduras where collected and marketed fuelwood is used by the residential sector in both urban and rural settlements. We argue that geospatial modeling, aimed at representing real situations more closely while integrating uncertainty, should be used in calculations of carbon savings from cookstove projects or fuel switching interventions. Highlights: A GIS tool "Mofuss" was developed to quantify non-renewable fuelwood extraction. Mofuss models the dynamic response of the vegetation to fuelwood use scenarios. Mofuss deals with uncertainties typical of data-poor landscapes. Savings in non-renewable woody biomass from reduced consumption are accounted.